Tinjauan Kelengkapan Pengisian Persetujuan Tindakan Kedokteran Pasien Bedah Rawat Inap di Rumah Sakit Umum Pusat Persahabatan - Ima Rusdiana (APIKES Bhumi Husada Jakarta, 2017)
ABSTRACT Medical informed consent is a consent given by the patient. Based on the regulation of Health Minister No 290/MENKES/PER/III/2008 article 1, what it means of Medical informed consent is a consent given by the patient or closest family member after given a thorough information regarding medical/dental procedures that will be done in the hospital. Formulation of the research conducted in Persahabatan Hospital is to review the completeness of filling the surgical informed consent for hospitalized patient in Persahabatan Hospital. The aims of this study are divided in to 2 which are general and specific. General purpose is to know the completeness of filling the surgical informed consent for hospitalized patient in Persahabatan Hospital, while the specific aim is identification of medical informed consent completion in Persahabatan Hospital and analyze the data. The method used in this study is by using descriptive methods. This method is done with main purpose of to give an objective image about the problem. Descriptive study is used to solve or answer the current problem. The result stated that completion of the medical informed consent is complete and running. However, it has not been socialized to the inpatient installation or other unit facilities. Based on the result of this study there are 56 samples of the medical informed consent on Februari 2011 in Persahabatan Hospital. From that samples, there are 68.87% complete filling and 29.94% incomplete filling. ABSTRAK Tujuan penelitian ini dibagi menjadi 2 umum dan khusus yaitu Mengetahui kelengkapan pengisian persetujuan tindakan kedokteran pasien bedah rawat inap di RSUP Persahabatan dan tujuan khususnya yaitu Mengidentifikasi SPO tetang pengisian persetujuan tindakan kedokteran di RSUP Persahabatan. Menganalisis kelengkapan pengisian persetujuan tindakan kedokteran pasien bedah rawat inap di RSUP Persahabatan. Metode yang digunakan untuk penulisan ini adalah menggunakan metode deskriptif yaitu suatu metode penelitian yang dilakukan dengan tujuan utama untuk membuat gambaran atau deskripsi tentang suatu keadaan secara objektif . metode penelitian deskriptif digunakan untuk memecahkan atau menjawab permasalahan yang sedang dihadap pada situasi sekarang. Kesimpulan hasil penelitian di RSUP Persahabatan bahwa SPO Pengisian Persetujuan tindakan kedokteran sudah ada dan lengkap. Tetapi belum di sosialisasikan ke instalasi rawat inap maupun unit-unit terkait lainnya. Berdasarkan hasil penelitian rekam medis tentang kelengkapan pengisian persetujuan tindakan kedokteran pasien bedah sebanyak 56 sampel rekam medis pasien rawat inap di RSUP Persahabatan. Dari hasil kelengkapan pengisian tersebut yang lengkap 69,87 % dan yang tidak lengkap 29,94 %.